Potential Development of Students and the Community Integrated by Al Baghdadi Islamic Boarding School Karawang - Iqbal Jamalulail; Sari Viciawati Machdum (International Journal Labs, 2022)
Pesantren is a Faith Based Organization (FBO) that is based on religion that has concern for human development. Empowerment in the Islamic boarding school area through the development of community and Santri potential in an integrated manner can improve and create a prosperous society in the economic sector in particular. This research aimed to describe and explain the development of students at the Al Baghdadi Islamic Boarding School in order to increase the potential of the community, the stages and steps of the school in increasing the community's potential, and the outcome of increasing the potential of students and the community. The method used in this study is a qualitative type with a phenomenological approach. This research was carried out at the Al Baghdadi Islamic Boarding School on Proklamasi Street, Sasak Hamlet, Amandari Village, Rengasdengklok District, Karawang Regency, West Java. As for data analysis with open codding, axial codding, and selective coding. The Al Baghdadi Islamic Boarding School carried out the following stages: are constructive and persuasive starting from preparation, social mapping, program planning, implementation, and evaluation where this stage is carried out continuously. Pesantren Al Baghdadi makes improvements to the community both in terms of skills, entrepreneurship, finance, and spirituality. The guidance carried out by the Al Baghdadi Islamic Boarding School for students and the surrounding community has several aspects: significant continuity. This can be seen from the observations that the community and the Pesantren are united. Society has dependence on Pesantren, and vice versa.